Simultaneous Quantification of Citalopram and its Main Metabolite, Desmethylcitalopram, in Human Saliva by UHPLC - Dziurkowska, Ewelina; Wesolowski, Marek (Current Analytical Chemistry, 2018)
Background: This study was designed to develop a reliable method for simultaneous quantitation of Citalopram (CIT) and its main active metabolite, Desmethylcitalopram (DCIT), in saliva of patients undergoing treatment with CIT. Methods: To compare two procedures of saliva purification, Solid-Phase (SPE) and Liquid-Liquid (LLE) extractions, saliva samples obtained from healthy volunteers were spiked with adequate quantities of CIT and DCIT. Different cartridges were used for SPE, while dichloromethane for LLE. Chromatographic separation and quantitation were carried out by UHPLC with DAD detector using a C-18 column and a mixture of acetonitrile and redistilled water (37:63, v:v) with the addition of formic acid (pH 3.5) as a mobile phase. Results: A comparison of both purification procedures showed that the most satisfactory results were obtained by SPE using Discovery C18 cartridge and redistilled water with formic acid (pH 3.5) as a washing solvent. Dichloromethane proved to be the best extractant in LLE. Both procedures enabled the separation of analytes from human saliva with high precision and recovery. Conclusions: Validation of the developed UHPLC procedure revealed that, regardless of how the sample was purified, the method was characterized by good linearity (between 10 and 1000 ng/mL), sensitivity, reproducibility, specificity and low values of limits of detection and quantitation. The limits of quantitation were 4.0 and 8.0 ng/mL for SPE and LLE, respectively. The efficiency of the method in therapeutic drug monitoring of CIT and DCIT in saliva of patients was confirmed.
Keywords: simultaneous UHPLC quantitation